1986
DOI: 10.1139/f86-168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Oxygen Concentration on Measurements of Sediment Oxygen Consumption

Abstract: j., and F. H. Rigler.. 1986. Effect of ambient oxygen concentration on measurements of sediment oxygen consumption. Can. ). Fish. Aquat. Sci. 43: 1340-1 349.The disparity between hypolimnetic oxygen depletion in situ (HOB; independent of the ambient oxygen coneentration), used to calculate sediment oxygen consumption (SOC) in one take in southern Quebec, and measurements of SOC (dependent on the oxygen concentration) was minimal when experimental factors were controlled. Using gas-tight methods, SOC at 7-5 mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Lasenby (1975) and Cornett & Rigler (1984) observed that hypolimnetic DO concentrations decreased linearly over time, independent of oxygen concentration. Conversely, Campbell & Rigler (1986) reported that ambient DO concentrations <2–3 g O 2 m −3 caused DO depletion rates to decline. The exclusion of volume‐weighted DO concentrations <2 g O 2 m −3 when calculating rates of DO depletion by linear regression prevented these anomalies affecting the resultant VHOD obs .…”
Section: Discussionmentioning
confidence: 98%
“…Lasenby (1975) and Cornett & Rigler (1984) observed that hypolimnetic DO concentrations decreased linearly over time, independent of oxygen concentration. Conversely, Campbell & Rigler (1986) reported that ambient DO concentrations <2–3 g O 2 m −3 caused DO depletion rates to decline. The exclusion of volume‐weighted DO concentrations <2 g O 2 m −3 when calculating rates of DO depletion by linear regression prevented these anomalies affecting the resultant VHOD obs .…”
Section: Discussionmentioning
confidence: 98%
“…In multilake studies of oxygen depletion, Lasenby (1975) and Cornett and Rigler (1984) observed that hypolimnetic DO concentrations decreased linearly with time, suggesting that the process of hypolimnetic oxygen depletion is independent of the ambient DO concentration. However, evidence also exists that DO concentrations Ͻ2-3 mg L Ϫ1 cause lower depletion rates (Cornett and Rigler 1984;Campbell and Rigler 1986). Burns (1995) recommends that hypolimnetic oxygen depletion rates should not be calculated for hypolimnia with DO concentrations Ͻ2-3 mg L Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
“…Campbell & Rigler (1986) investigated the dependence of AT S on oxygen concentrations and they concluded that A" s was independent of ambient oxygen concentration above 3 g m~3, but that K^ varied with oxygen concentration below that level with the dependence showing up more strongly below 2 g m 3 . In experiments on the dependence of K w on ambient oxygen levels, Cornett & Rigler (1984) found dependence existed only below 2 g m~3.…”
Section: Process 1: Effects Of Ambient Dissolved Oxygen (Do) Concentrmentioning
confidence: 99%